Leucine‐rich repeat‐containing G protein‐coupled receptor 5 expression in ductular reactions after chemotherapy for metastatic colorectal cancer. Issue 1 (18th January 2013) - Saigusa, Susumu; Tanaka, Koji; Toiyama, Yuji; Matsushita, Kohei; Kawamura, Mikio; Okugawa, Yoshinaga; Uchida, Keiichi; Inoue, Yasuhiro; Mohri, Yasuhiko; Kusunoki, Masato
<x xml:space="preserve">Abstract</x> Aim: Oval cells with ductular reactions (DR) in damaged liver are referred to as "intermediate hepatobiliary cells". In a preliminary study, we had found expression of the leucine‐rich repeat‐containing G protein‐coupled receptor 5 (LGR5) known as a potential marker for stem cells in the small intestine and colon in DR in liver damaged by chemotherapy for metastatic colorectal cancer (CRC). The aim of this study was to confirm LGR expression in DR in damaged liver after chemotherapy. Methods: A total of 68 liver specimens obtained after surgical resection were stained with monoclonal antibodies for cytokeratin (CK)7, neural cell adhesion molecule (NCAM; a bile ductular and liver progenitor cell marker), CD133 (a candidate stem cell marker of hepatocellular carcinoma as well as CRC) and LGR5. Additionally, these mRNA levels were investigated according to the location in damaged liver after chemotherapy using microdissected specimens. Results: We observed that LGR5 was expressed in DR with CD133, CK7 and NCAM expression. By contrast, LGR5, CD133 and NCAM were not expressed in mature bile ducts with CK7. In transcriptional analysis, LGR5 mRNA levels in fibrotic tissue including DR were higher compared with that in adjacent normal liver without significant difference. Conclusion: These findings suggest that LGR5 may be involved in maintaining DR in damaged liver.